Development of coupled enzyme assay and in vitro synthetic biology approach for glycosylation pathway characterization - Nashed, Abdullateef (Department of Chemistry, 2025)
Glycans play essential roles in living organisms that encompass a wide range of biological functions ranging from energy metabolism all the way through to intricate cell signalling pathways. They carry out these functions either directly by participating in metabolism and binding or indirectly by altering the structure and nature of their conjugates, for example by being the major posttranslational modifier of proteins. The family of glycans in a biological organism (the glycome) correlates to the system's state. In this thesis the focus is the development of methods and measures to model the correlation of aberrant glycosylation of MUC1 that is associated with certain cancers. Central to this is an accurate MUC1 peptide monomer and associated glycosyltransferases (GTs) able to be deployed in specific construction. However, deconstructing the machinery of the GTsubstrate interactome is challenging because of the complexity of glycan structures and the diversity of GTs acting on them. Two tool sets that can advance our understanding is the development of reliable kinetic assays and constructing biologically relevant substrate arrays. Presently used assays are disadvantaged by either being endpoint assays or continuous ones compromised by lack of specificity and sensitivity, or have high cost. Chemically synthesized glycan arrays often face insurmountable hurdles of complex carbohydrate chemistry. To address these challenges, the work undertaken in this thesis was firstly the development of a continuous enzymatic-coupled assay through the redesign of the pyruvate kinase/lactate dehydrogenase (PK/LDH)-coupled assay that lead to increasing the sensitivity and specificity of detection. Further the assay was adapted to accommodate all classes of GTs. Secondly, an in vitro synthetic biology approach was developed to construct a MUC1 O-glycans model peptide as a proof-of-concept of a seamless “one pot” glycopeptide synthesis strategy. Here a fusion protein, consisting of the MUC1 core peptide and a carrier protein, was designed for expression in E. Coli.. The fusion protein elements were optimized to maximize solubility, facilitate without obstruction the in vitro enzymatic glycosylation of the peptide, and enable the recovery of the products through a simple one-step purification. The peptide in the fusion protein was optimized to undergo in vitro sequential enzymatic glycosylation that replicates the native pathway. The properties of the fusion proteins enabled investigation of the activities of the downstream GTs on the synthesized peptides in their fusion forms, which was used in the investigation of the site specificity of ST6GALNAC1, and its role in the biosynthesis of the breast cancer marker STn.